Where Are We? The State of Education (LEARNing Landscapes, 2010)
Today the questions that should be asked about schools and schooling are those that take into account the social context in which we live. We need to attend to the world outside of the closed context of the "system" and recognize the ways in which the world is interrelated. We need to understand that each and every student comes to the classroom with a biography and a way of being in the world. For today’s young learners that world is a wired one in which social interaction can be conducted anywhere, any place, or anytime. A key challenge for educators is to adapt the institutions in which they work to meet the emerging reality of the connected environment. If we do not manage to make this adaptation, then the future of public education is bleak.
Keywords: education; school; social context; technology; system; connected environment; young learner